2021
DOI: 10.52312/jdrs.2021.298
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of scaphoid fracture osteosynthesis with magnesium screws

Abstract: Objectives This study aims to evaluate the mid-term functional and radiological outcomes of magnesium-based screws in the treatment of scaphoid fractures. Patients and methods Between February 2015 and February 2018, a total of 21 patients (18 males, 3 females; mean age: 28.5±5.8 years; range, 19 to 39 years) with acute scaphoid waist fractures who underwent fracture fixation with biologically degradable magnesium-based compression screws were retrospectively analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…On the other hand, Mg 2+ promotes osteogenesis by promoting inflammatory immune microenvironment in the early stages of osteogenesis. Previous research has found that alginate hydrogels that sustain the release of Mg 2+ contributed to the infiltration and activation of CD68 + macrophages in bone defects during the early stages of bone healing [ 22 , 23 ]. They also found that Mg 2+ promoted the expression of the transient receptor potential cation channel M7 (TRPM7) and nuclear translocation of TRPM7 cleaved kinase fragments (M7CKs), leading to the differentiation of macrophages into the osteogenic subtype as well as promoting bone marrow recruitment and osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Mg 2+ promotes osteogenesis by promoting inflammatory immune microenvironment in the early stages of osteogenesis. Previous research has found that alginate hydrogels that sustain the release of Mg 2+ contributed to the infiltration and activation of CD68 + macrophages in bone defects during the early stages of bone healing [ 22 , 23 ]. They also found that Mg 2+ promoted the expression of the transient receptor potential cation channel M7 (TRPM7) and nuclear translocation of TRPM7 cleaved kinase fragments (M7CKs), leading to the differentiation of macrophages into the osteogenic subtype as well as promoting bone marrow recruitment and osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum release of 42 mg/L in the pure substrate was observed on the third day of immersion, followed by the aloe vera-loaded sample with 31.5 mg/L and the PLA-coated sample with a 20.7 mg/L Mg ions release rate. Afterward, this release rate seemed to reduce due to the oxide layer developed across the substrate, which restricted the Mg ions release into the immersion medium [66,67]. In the case of the aloe vera loaded sample, a possible reason for an initial burst of Mg ions can be the surface abrasion of the substrate when it was in contact with the corrosion medium.…”
Section: Corrosion Propertiesmentioning
confidence: 99%
“…[ 8 ] Recently, alternative bioabsorbable magnesium-based screws have been introduced in orthopedic surgery. [ 9 ] Several studies[ 10 , 11 ] have compared biodegradable magnesium screws with metal screws in patients undergoing DMO. However, whether biodegradable magnesium screws are effective and safe as metallic screws in DMO still remains controversial.…”
Section: Introductionmentioning
confidence: 99%